Organizational Performance: Concerns in Construct Measurement - Mekoth, Nandakumar; Barnabas, N (Ushus Journal of Business Management, 2005)
There is no consensus among researchers on the definition and measurement practices of Organizational Performance. Some suggest that it is best left as a conceptually rather than empirically relevant construct.